Essential or redundant? Disentangling the (GR)ESAG families of Trypanosoma brucei - Chamberlain, James W. (2018)
The protozoan parasite Trypanosoma brucei escapes its mammalian host’s immune response by switching expression of its major surface antigen, variant surface glycoprotein (VSG), which forms a protective coat around the cell. The actively expressed VSG is transcribed from one of 14 bloodstream expression sites (BESs), which also encode variable repertoires of expression site associated genes (ESAGs), most of which localise to the parasite surface. These genes form distinct families, are co-transcribed with VSG, and the repertoire expressed changes upon in situ switch. Specific ESAGs are known to protect the parasite from human serum lytic effects, modulate the host’s innate immune response, mediate uptake of essential nutrients, and may adapt the parasite to the serum of different mammalian hosts. In addition to BES-linked ESAGs, these families also encompass non-BES encoded genes related to ESAGs (GRESAGs), some of which, unlike the ESAGs, are expressed in both mammalian and insect lifecycle stages.